Study of Scour Characteristics Downstream of Partially-Blocked Circular Culverts - Nesreen Taha (Water, 2020)
Debris accumulations upstream and through crossing hydraulic structures such as culverts cause the upstream water level and the downstream scour depth to increase, which can lead to structure failure. This experimental study aimed to investigate the effects of various inlet blockage ratios on culvert efficiency and scour hole depth. In a non-blocked case, various submergence ratios (S = 1.06, 1.33, 1.60, and 1.90) were tested with different discharge rates. In a blocked case, the effects of inlet blockage with various blockage ratios (Ar = 10%, 20%, and 30%) were seen as sediment blockage on the pipe bed or floating debris upstream of the culvert. The results show that as the submergence ratio increases, the maximum scour depth decreases at the same discharge rate, and the relative energy loss also decreases in the non-blocked case. In the sediment blockage (Ar d) case, the relative maximum depth increases with increasing densimetric Froude number and with an increasing blockage ratio. An empirical equation was developed to predict the relative scour depth under the present study conditions.